The Polaron Effects and Temperature Dependence of the Strong-Coupling Exciton in Slab of Polar Crystals (Journal of Atomic and Molecular Sciences, 2013)
The system, in which the excitons interact with both the weak-coupling bulk longitudinal-optical (LO) phonons and strong-coupling surface-optical (SO) phonons in a slab of polar crystal, is studied by using a linear combination operator and the Lee-Low-Pines variational method. The expression of the induced potential of the exciton is derived, and the numerical calculations for the AgBr crystal as an example are made. The results show that the induced potential of the exciton relates not only to the distance between electron and hole, but also to the thickness of slab and temperature.
Keywords: exciton; strong-coupling; induced potential.